2018
DOI: 10.17576/jem-2018-5202-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sustainability Certification for Export on Operational Profitability of Malaysian Palm Oil Companies

Abstract: Malaysia is the world's second largest palm oil producer with 17.4 million tonnes palm oil produced in 2016. The production is for both domestic and export which contribute towards country's income and economic growth. Despite the significant contribution to the economy, being one of the plantation sectors, Malaysian palm oil has been criticized by the western communities for causing environmental problems such as deforestation and open burning. Hence, it is important for the palm oil companies to ensure susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
5
0
4
Order By: Relevance
“…This is different from small companies with limited funding sources and uses internal financing because of the high costs and risks [41]. Previous research found that firm size has an impact on company performance [15,42]. • Firm Age.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…This is different from small companies with limited funding sources and uses internal financing because of the high costs and risks [41]. Previous research found that firm size has an impact on company performance [15,42]. • Firm Age.…”
Section: Methodsmentioning
confidence: 98%
“…Previous research has investigated the performance of palm oil companies in Malaysia and found a positive effect of sustainable certification on palm oil companies' profitability performance [25]. Other studies have found that sustainable certification for exports has no impact on palm oil companies' operational performance in Malaysia [15]. The timing in adopting RSPO certification influences the profitability of the palm oil companies [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-Governmental Organization (NGO) juga turut serta dalam meningkatkan tekanan terhadap industri sawit dengan mendorong kewaspadaan konsumen dan perusahaan terhadap dampak negatif yang ditimbulkan pada produksi kelapa sawit. Pada akhirnya, peningkatan tekanan konsumen internasional berujung pada diperkenalkannya skema sertifikasi untuk memproduksi minyak sawit yang berkelanjutan (Brandi et al, 2013;Shahida et al, 2018) Salah satu sertifikasi keberlanjutan kelapa sawit adalah Roundtable on Sustainable Palm Oil (RSPO) yang didirikan pada tahun 2004. RSPO merupakan organisasi nirlaba yang menyatukan kepentingan pelaku pada industri sawit diantaranya produsen, pengolah atau pedagang kelapa sawit, produsen barang konsumsi, pengecer, bank atau investor, dan Lembaga Swadaya Masyarakat (LSM) untuk menerapkan standar global dalam produksi minyak sawit berkelanjutan (RSPO, 2022).…”
Section: Pendahuluanunclassified
“…Penentuan variabel dependen dalam penelitian ini merujuk kepada beberapa penelitian terdahulu (Tabel 1). Model ekonometrika dalam penelitian ini merupakan adopsi dari studi Shahida et al (2018), Hafizuddin-Syah et al (2018) dan Ramasamy et al, (2005) serta dikembangkan sesuai dengan kebutuhan analisis. Model ekonometrika yang digunakan dalam penelitian ini dirumuskan sebagai berikut:…”
Section: Metodeunclassified